Tick-host conflict: immunoglobulin E antibodies to tick proteins in patients with anaphylaxis to tick bite - Mateos-Hernández, Lourdes; Villar, Margarita; Moral, Angel; Rodríguez, Carmen García; Arias, Teresa Alfaya; de la Osa, Verónica; Brito, Francisco Feo; Fernández de Mera, Isabel G; Alberdi, Pilar; Ruiz-Fons, Francisco; Cabezas-Cruz, Alejandro; Estrada-Peña, Agustín; et al. (Oncotarget, 2017)
Tick-borne infectious diseases and allergies are a growing problem worldwide. Tick bite allergy has been associated with the direct effect of immunoglobulin E (IgE) response to tick salivary antigens, or secondary to the induction of allergy to red meat consumption through IgE antibodies against the carbohydrate α-Gal (Gal α 1-3Gal β 1-(3)4GlcNAc-R). However, despite the growing burden of this pathology, the proteins associated with anaphylaxis to tick bite have not been characterized. To address this question, a comparative proteomics approach was used to characterize tick proteins producing an IgE antibody response in a healthy individual with record of tick bites, which had not resulted in any allergic reactions, and two patients with anaphylactic reactions to Rhipicephalus bursa or Hyalomma marginatum tick bites. Both patients and the healthy individual were red meat tolerant. The results supported a patient-specific IgE antibody response to tick species responsible for the anaphylaxis to tick bite. Both patients and the healthy individual serologically recognized tick proteins with and without α-Gal modifications, with proteins differentially recognized by patients but not control sera. These proteins could be used as potential antigens for diagnostics, treatment and prevention of tick bite-induced allergies.
Keywords: Arthropod Proteins; Immunity; lidé středního věku; allergy; Animals; Antigens; mužské pohlaví; anafylaxe; Tick Bites; proteomika; Anaphylaxis; Humans; Immunoglobulin E; Immunology and Microbiology Section; anaphylaxis; alpha-Gal; Ticks; Electrophoresis, Gel, Two-Dimensional; Immune response; lidé; Male; Blotting, Western; kousnutí klíštětem; Middle Aged; imunoglobulin E; Proteomics; zvířata; proteomics; 2D gelová elektroforéza; proteiny členovců; klíšťata; western blotting; immunology; antigeny